2018
DOI: 10.1371/journal.pntd.0006817
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of dengue in relation to dengue serotype and genotype in Malaysia: A retrospective observational study

Abstract: BackgroundMalaysia experienced an unprecedented dengue outbreak from the year 2014 to 2016 that resulted in an enormous increase in the number of cases and mortality as compared to previous years. The causes that attribute to a dengue outbreak can be multifactorial. Viral factors, such as dengue serotype and genotype, are the components of interest in this study. Although only a small number of studies investigated the association between the serotype of dengue virus and clinical manifestations, none of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 26 publications
9
58
0
5
Order By: Relevance
“…Clinical findings in our patients appear more consistent with dengue in adults rather than dengue caused specifically by DENV-1, which is often associated with lower rates of arthralgia and myalgia (Burattini et al 2016;Martins Vdo et al 2014;Suppiah et al 2018;Yung et al 2015).…”
Section: Discussionsupporting
confidence: 64%
“…Clinical findings in our patients appear more consistent with dengue in adults rather than dengue caused specifically by DENV-1, which is often associated with lower rates of arthralgia and myalgia (Burattini et al 2016;Martins Vdo et al 2014;Suppiah et al 2018;Yung et al 2015).…”
Section: Discussionsupporting
confidence: 64%
“…Leptospirosis co-infection with dengue or scrub typhus is commonly seen in neighbouring countries such as Thailand and India [36][37][38][39][40][41][42][43]. Dengue is highly endemic in Malaysia with a minimum of 100,000 cases and more than 200 mortalities every year [44]. A recent study by Suppiah et al (2017) reported 11/268 (4.1%) dengue cases to be co-infected with leptospirosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been done to figure out the relationship between the dengue serotypes and their respective clinical manifestations. Infection with DEN-1 and DEN-3 has mild clinical manifestations, whereas infection cases with DENV-2 showed severe manifestations amongst all [5] . The infection varies from asymptomatic illness to severe ones such as haemorrhagic fever and dengue shock syndrome.…”
Section: Introductionmentioning
confidence: 95%
“…Meanwhile DENV-2 was first reported in Indonesia and Papua New Guinea and spread thru Asian regions such as Malaysia, Thailand, the Philippines and Singapore since then. Both DENV-3 and DENV-4 were reported much later in 1953 in the Philippines and Thailand [5] .…”
Section: Introductionmentioning
confidence: 99%